Primitive decapods from the deep sea: first record of blind lobsters (Crustacea: Decapoda: Polychelidae) in northeastern Brazil - Luis Ernesto Arruda Bezerra; Felipe Bezerra Ribeiro (Nauplius)
ABSTRACT We report herein the occurrence of the infraorder Polychelida in Potiguar Basin, northeastern Brazil. Specimens were collected by the project "Avaliação da Biota Bentônica e Planctônica na porção offshore das Bacias Potiguar e Ceará", developed by the Brazilian Oil Company (PETROBRAS). Three species were recorded for the first time in this region: Pentacheles validus A. Milne-Edwards, 1880, Polycheles typhlops Heller, 1862, and Stereomastis sculpta (Smith, 1880) at 2000 m, 400 m and 2057 m depth, respectively. The Brazilian deep-sea floor remains poorly known, but progress has been made as a result of collections obtained by oceanographic expeditions and research projects developed by PETROBRAS in Campos Basin (Rio de Janeiro) and Potiguar Basin (Rio Grande do Norte), expanding the knowledge of the distribution area of Polychelidae in Brazilian deep sea waters.